2013
DOI: 10.1002/ca.22286
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the YESS and TESSYS techniques of percutaneous transforaminal endoscopic lumbar discectomy

Abstract: Posterior lateral endoscopic nucleotomy is widely accepted as a minimally invasive surgery for lumbar disc herniation, but few studies have compared the transforaminal approach using two different techniques, YESS and TESSYS. One hundred and fifty lumbar IVFs of cadaveric spines were studied. Eighteen-gauge needles were inserted percutaneously toward IVFs into the discs by either YESS or TESSYS. The distances from the needle to the nerve root and from the needle to the spinal dura were measured and compared ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…19 In this study, the mean distance from the dura to the nerve root at the level of the superior endplate (distance b) was 13.64 ± 2.52 mm (range, 9.30-21.20 mm), which was relatively smaller than that of cadaveric analysis. Mirkovic et al 10 defined the "safe zone" as 18.9 mm wide and 12.3 mm high based on the cadaveric study, and the size increased as going down the level of spine.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…19 In this study, the mean distance from the dura to the nerve root at the level of the superior endplate (distance b) was 13.64 ± 2.52 mm (range, 9.30-21.20 mm), which was relatively smaller than that of cadaveric analysis. Mirkovic et al 10 defined the "safe zone" as 18.9 mm wide and 12.3 mm high based on the cadaveric study, and the size increased as going down the level of spine.…”
Section: Discussionmentioning
confidence: 54%
“…5). 19 In a study of 280 cases of transforaminal endoscopic disectomy, Hoogland et al 20 found that the incidence of contact between the instrument and the nerve root was 57.6% during YESS procedure; however, only 36.2% during TESSYS procedure. Unlike YESS technique, the puncturing target of TESSYS approach is the isthmus of the upper lamina or the facet joints (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, conventional open surgery occasionally requires a wider facetectomy, and the risk of postoperative instability increases (15). Anatomical cadaver studies clearly indicated that more medial access to Kambin's triangle by foraminoplasty not only provides safe access to the intra-canal or foraminal space but also makes it possible to prevent exiting nerve injury (17). Therefore, foraminoplasty (removal of SAP from outside to medial, thereby enabling endoscopic access to the medial part of the triangle) using a surgical burr or trephine is an appropriate option in PLA for PELD.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10,15 Mirkovic et al described the dimensions of the safe margins for a working cannula in the neural foramen in 1995 and determined that a cannula placed in line with the medial one-third of the pedicle could sustain a safe average diameter of 7.5 mm. 10 Min et al in 2005 determined the mean distance between the exiting nerve root and the superior articulating process to be 11.6 mm, which is sufficiently smaller than our own determination of 15.5 mm for the average distance between the exiting and traversing nerve roots at the top of the base of the working triangle with the superior articulating process removed.…”
Section: Fig 3 Mean Area (Cmmentioning
confidence: 99%